Re-Evaluation of Acid-Base Prediction Rules in Patients with Chronic Respiratory Acidosis - Tereza Martinu; Dick Menzies; Sandra Dial (Canadian Respiratory Journal)
RATIONALE: The prediction rules for the evaluation of the acid-base status in patients with chronic respiratory acidosis, derived primarily from an experimental canine model, suggest that complete compensation should not occur. This appears to contradict frequent observations of normal or near-normal pH levels in patients with chronic hypercapnia.